Kemampuan Representasi Matematis Siswa dalam Pembelajaran Flipped-Project-Based Learning - Bayu Tri Handoko; Mulyono Mulyono; Isnaini Rosyida (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
The goal of this study is to see how effective flipped-project-based learning models are at improving students' mathematical representation skills in class X at SMK Negeri 1 Jepon, Blora Regency. This study is quantitative research with an experimental method and uses a true experimental design with a pretest-posttest control group design strategy. This study focuses on students in class X at SMK Negeri 1 Jepon, Blora Regency during the academic year 2021/2022. A mathematical representation skills test was employed as a data collection approach before and after studying trigonometric content. The average difference test, individual completeness test, classical completeness test, and skills improvement test were all used in the data analysis. The average value of mathematical representation skills in the experimental class is 73.85, higher than the average value of mathematical representation skills in the control class, 70.10; the average value of mathematical representation skills in the experimental class is 73.85, higher than the minimum completeness criterion of 70; the proportion of students' completeness in the experimental class is 89%, higher than 75%; and the proportion of students' completeness in the experimental class is 73.85 and an increase in the skills of mathematical representation in the experimental class with moderate criteria